Compound Nouns as Cognitive Artifacts Language, Thought, and Culture in English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the cognitive underpinnings of compound noun formation in English, with a particular focus on the continuum between semantic transparency and opacity. Compound nouns, ranging from transparent forms like "teacup" to opaque constructions like "humbug," provide valuable insights into the cognitive mechanisms involved in language processing, including metaphor, metonymy, and conceptual integration. The paper examines how these mechanisms contribute to the development of polysemy in compound nouns, facilitating the transition from literal to figurative meanings. Through case studies of zoonymic (animal-based) and phytonymic (plant-based) compounds, it highlights the dynamic nature of compound interpretation across various registers, from formal to informal and slang. The analysis demonstrates how compound nouns not only function as linguistic tools but also reflect cognitive processes and cultural contexts, enriching both vocabulary and symbolic meaning. Ultimately, this research deepens our understanding of how conceptual strategies shape language use and offers a comprehensive view of the cognitive processes that underlie compound noun formation in English.